3(а-1) / √(а²+2а-3)
Объяснение:
Чтобы избавиться от иррациональности в числителе, необходимо домножить и числитель и знаменатель на числитель:
3√(а-1) / √(3+а)= 3√(а-1)*√(а-1) / √(3+а)*√(а-1)= 3(а-1) / √((3+а)(а-1))= 3(а-1) / √(3а-3+а²-а)= 3(а-1) / √(а²+2а-3)
3(а-1) / √(а²+2а-3)
Объяснение:
Чтобы избавиться от иррациональности в числителе, необходимо домножить и числитель и знаменатель на числитель:
3√(а-1) / √(3+а)= 3√(а-1)*√(а-1) / √(3+а)*√(а-1)= 3(а-1) / √((3+а)(а-1))= 3(а-1) / √(3а-3+а²-а)= 3(а-1) / √(а²+2а-3)